2020
DOI: 10.1111/ajco.13386
|View full text |Cite
|
Sign up to set email alerts
|

The venous thromboembolism prophylaxis in patients receiving thoracic surgery: A systematic review

Abstract: Objectives: Venous thromboembolism (VTE) is a significant and preventable cause of mortality and morbidity in thoracic surgery. It usually deep venous thromboembolism (DVT) and pulmonary thromboembolism (PE). We conducted this article to perform a systematic review on prophylaxis of perioperative VTE in patients undergoing thoracic surgery especially lung surgery and esophageal surgery and to identify potential areas for future research. Methods:The systematic review we conducted included studies of patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…VTE is a major source of postoperative morbidity and mortality for patients undergoing thoracic surgery. 20 , 21 VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE. 22 , 23 , 24 In addition, most VTE events in this study were found in the lower extremities which is in agreement with previously reported studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…VTE is a major source of postoperative morbidity and mortality for patients undergoing thoracic surgery. 20 , 21 VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE. 22 , 23 , 24 In addition, most VTE events in this study were found in the lower extremities which is in agreement with previously reported studies.…”
Section: Discussionmentioning
confidence: 88%
“…VTE is a common complication for lung adenocarcinoma patients who undergo surgery, especially during the perioperative process and hospitalization. VTE is a major source of postoperative morbidity and mortality for patients undergoing thoracic surgery 20,21 . VTE events mostly occur during hospitalization, including the perioperative period, and subsequent examinations or treatments, which support that hospitalization is an independent risk factor for VTE 22–24 .…”
Section: Discussionmentioning
confidence: 98%
“…Venous thromboembolism (VTE) is a common disease with multiple factors and high mortality caused by venous blood stasis syndrome, vascular endothelial cell injury, hypercoagulable state and so on. [ 15 , 16 ] Severe venous thromboembolism in the acute stage can lead to lower limb gangrene and even fatal pulmonary embolism, which is a direct threat to the safety of patients. Anticoagulant therapy is the main treatment, and surgical thrombectomy is feasible in severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…A history of VTE, getting older, being obese, having left or right ventricular failure, being mechanically ventilated for an extended period, using a central venous catheter, and not using any anticoagulant or antiplatelet medications are all risk factors for VTE after cardiac surgery. [31][32][33] The occurrence of DVT and PE during digestive surgery is expected to range from 2.75 to 8.9%, with colorectal cancer and inflammatory bowel disease being the primary risk factors. For liver resection and significant abdominal surgery without prophylaxis, the prevalence of VTE was 0.7 and 0.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%